2016
DOI: 10.1007/s00421-016-3406-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and testosterone dynamics following exhaustive endurance exercise

Abstract: EES recovery may require 48 h for C and 72 h for fT to return to baseline values. Furthermore, C and fT were only correlated immediately post-exercise. Future research should perform more frequent measurements throughout time course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 26 publications
(35 reference statements)
3
57
1
Order By: Relevance
“…The TT/C ratio has been reported as an indicator of anabolic/catabolic homeostasis and overtraining [6,[34][35][36][37][38][39][40][41][42][43][44][45]. These authors assert that the ratio between these two hormones is known as the free testosterone/cortisol ratio (FT/C), and that free testosterone is defined as testosterone not linked to any proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The TT/C ratio has been reported as an indicator of anabolic/catabolic homeostasis and overtraining [6,[34][35][36][37][38][39][40][41][42][43][44][45]. These authors assert that the ratio between these two hormones is known as the free testosterone/cortisol ratio (FT/C), and that free testosterone is defined as testosterone not linked to any proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2014) reported that IMO significantly enhanced the serum corticosterone about fourfold ($1.554 Â 10 À6 M, compared with the resting concentration near 2.88 Â 10 À7 M) and decreased the serum testosterone level in rats. Other evidence emphasized that hyper-CORT level leads to decrease testosterone concentration in human under exhaustive endurance exercise (Anderson et al, 2016) and in mice under IMO (Dong et al, 2004). To date, the combination effect of CORT plus lactate on testosterone production and relative mechanisms in steroidogenesis is remaining unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the first mechanism, Doerr and Pirke, as well as Cummings and associates, demonstrated blood cortisol elevations disrupt testosterone production peripherally at the gonad (testes) when cortisol levels were elevated (78,79). There are numerous research studies reporting findings of exerciseinduced short-term increases in cortisol levels (see review articles-references (74, 78)), as well as these acute elevations in cortisol from an exercise session being associated with decreases in testosterone (72,80,81). Furthermore, evidence exists for circulating testosterone and cortisol to be negatively associated with athletes even in the resting, basal state (82).…”
Section: Overtraining Syndromementioning
confidence: 99%
“…Acute exercise-induced elevations in prolactin have been associated with testosterone reductions (87), as have training-induced increases in resting, basal prolactin associated with testosterone reductions (73,88); but the latter is not universally reported (41,89). Nevertheless, resting hypercortisolemic or hyperprolactinemic states are not frequently found in athletes, but consistent daily exercise sessions could create frequent transient periods of such hyper-exposure during an actual exercise session as well as for extended periods in the recovery from such exercise sessions (80,84,90,91).…”
Section: Overtraining Syndromementioning
confidence: 99%